2001
DOI: 10.1063/1.1334922
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of interfacial Si–oxide layers during postannealing of Ta2O5/Si

Abstract: The Si–O–Si bonds formed at the Ta2O5/Si interface by annealing were investigated by using Fourier transform infrared absorption spectroscopy. The Ta2O5 thin films deposited on Si substrates were annealed in different ambient (H2O, O2, and N2) at temperatures between 500 and 800 °C. When annealing is done in H2O, the interfacial silicon–oxide grows very rapidly, because the oxidation species can easily diffuse through Ta2O5 films, and because the Si–O formation is controlled by the diffusion of H2O in the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The surface morphology was evaluated by contact mode atomic force microscopy ͑AFM͒ on a Park Scientific Instrument ͑PSI͒ Autoprobe Research over a scanned area of 5 m ϫ 5 m. The dielectric properties of the thin films deposited at 550°C under different biases were measured using an Agilent 4396B type impedance analyzer. 16 In our experiments, the substrate bias does not affect the deposition temperature but aids to increase the nuclei density in the thin films. [13][14][15] Furthermore, the weak absorption bands at around 720 cm −1 of Zr-O-Si and 800 and 1080 cm −1 of the Si-O vibration mode occur at lower substrate biasing such as 0 and Ϫ100 V, implying the formation of very little SiO x and ZrSiO x at the interface.…”
Section: Methodsmentioning
confidence: 68%
“…The surface morphology was evaluated by contact mode atomic force microscopy ͑AFM͒ on a Park Scientific Instrument ͑PSI͒ Autoprobe Research over a scanned area of 5 m ϫ 5 m. The dielectric properties of the thin films deposited at 550°C under different biases were measured using an Agilent 4396B type impedance analyzer. 16 In our experiments, the substrate bias does not affect the deposition temperature but aids to increase the nuclei density in the thin films. [13][14][15] Furthermore, the weak absorption bands at around 720 cm −1 of Zr-O-Si and 800 and 1080 cm −1 of the Si-O vibration mode occur at lower substrate biasing such as 0 and Ϫ100 V, implying the formation of very little SiO x and ZrSiO x at the interface.…”
Section: Methodsmentioning
confidence: 68%
“…Among them, HfO 2 and ZrO 2 are the potential candidates. This produces rugged surfaces, 5 which are the sources of weak points where local electric fields are enhanced causing increased leakages, deterioration, and breakdown of the MOS structure. 3 Consequently, the thermodynamic stability of high-k metal oxide in contact with silicon is a critical issue for the application of alternative gate dielectrics in ultralarge scale integration ͑ULSI͒ devices.…”
Section: Introductionmentioning
confidence: 99%
“…Fur- indicating that at a higher substrate biasing, the interfacial structure of the ZrO 2 /Si thin films can be optimized. Ono et al suggested that the formation of the interfacial layers depended on neither the thickness of oxide films nor the annealing atmosphere, but rather the deposition or annealing temperature [20]. In our experiments, the substrate bias does not affect the deposition temperature but aids to increase the nuclei density in the thin films and reduce the critical nucleation energy [15].…”
Section: Methodsmentioning
confidence: 83%